Quality Physical Education and Global Concern – Ways Ahead and Future Development - King Yan Ho, Walter; Ahmed, Md. Dilsad; Wong, Beatriz; Huang, Fan; de D’Amico, Rosa; Dinold, Maria; Antala Branislav (ACTIVIDAD FÍSICA Y CIENCIAS / PHYSICAL ACTIVITY AND SCIENCE, 2022)
The works for quality development of physical education turned to be a worldwide concern when UNESCO proposed the International Charter for Physical Education and Sport in 1978. The movement for quality physical education was then established with main focus on different perspectives that covered issues from human right to the curriculum development, teaching, sport coaching, professional training, research and international collaboration and related policy making. The coming of documents such as NASPER’s benchmark in physical education in 2004, UNESCO Report on Quality of Physical Education and Sport (2005), Strategies to Improve the Quality of Physical Education by CDC in 2010 and the recent Quality Physical Education – Guidelines for Policy Makers by UNESCO (2015) were the initiatives to provide rich resources in forming the basic framework for quality development of physical education. Nevertheless, the report on physical education by Ken Hardman in 2008 indicated the worry as “mixed messages” was presented due to strong evidence of national commitment on physical education but slow to transform this initiation with full action and concrete implementation plan. “What goes wrong?” seemed to be the question that needs a response if the quality development of physical education is regarded as the way to improve the quality of students’ learning. The four association members of ICSP (ISCPES, IAPESGW, IFAPA and FIEP) launched a research project on Quality Physical Education (QPE) in 2011 with aims to understand the concept of QPE. This paper shared the findings from the QPE research and illustrated about the possible strategies for future development of QPE in schools. Proper investment and appropriate strategies with innovative works on steps and phases seemed to be the best option for development of core elements in QPE. While those elements there were in improvement stage, substantial Walter King Yan Ho, Md. Dilsad Ahmed, Beatriz Wong, Fan Huang, Rosa de D’Amico....Quality Physical Education and School Sports Development – A Global Study Revista Electrónica Actividad Física y Ciencias, Año 2016 Vol. 8 Nº 1 61 work to maintain its provision seemed essential. Keywords